Characterizing the Impact of the RNA Demethylase ALKBH5 on Hematopoietic Stem and Progenitor Cells - Hasan, Tanvir (Université d'Ottawa / University of Ottawa, 2023)
The RNA demethylase, ALKBH5, is a known prognostic factor in various diseases as well as critical in maintaining the leukemia initiating cells in acute myeloid leukemia. However, its role in normal hematopoiesis is unclear to date. Herein, I investigated the role of ALKBH5 in the context of human umbilical cord blood (CB) derived hematopoietic stem and progenitor cell (HSPC) self-renewal and differentiation in ex-vivo cultures and in-vivo systems. ALKBH5 expression was reduced in CB HSPCs using RNA interference (RNAi) strategy to interrogate the kinetic, phenotypic, and functional contribution of ALKBH5 in ex-vivo and invivo models of normal hematopoiesis. Deficiency of ALKBH5 led to higher (2.1-fold, P<0.05) expansion in the CD34+CD45RA- cell population compared to scramble control. Alternatively, hematopoietic stem cell enriched (eHSC, CD34+CD45RA-CD90+CD49f+) population was diminished (P<0.05) in ALKBH5 deficient samples. Functional capacity to produce colonies in colony forming assays was reduced by 1.5 times (P<0.05) in ALKBH5 deficient samples. Finally, in-vivo mice transplantation data show reduced long-term engraftment (3-times lower platelet concentration in peripheral blood, P <0.05) as well as altered human multi-lineage chimerism formation in the recipient of ALKBH5 reduced HSPCs. Thus, my experimental results demonstrate hitherto unexplored roles of ALKBH5 in regulating normal function of HSPCs. These findings underscore the need to further investigate ALKBH5 to improve our understanding of stem cell biology and to develop targeted therapies for diseases like leukemia.
Keywords: RNA demethylase; ALKBH5; Hematopoietic stem and progenitor cells; ex-vivo cell culture; cord blood; xenotransplantation; flow cytometry; N6-methyladenosine; Lentiviral knockdown